Morphology vs Genetics: the hybrid origin of a sea turtle disproved by DNA - GAROFALO, L.; ZACCARONI, A.; SCARAVELLI, D.; INSACCO, G.; ZANGRILLI, M.P.; NOVELLETTO, A.; LORENZINI, R. (Mediterranean Marine Science, 2012)
A putative hybrid sea turtle juvenile was evaluated with discriminant DNA markers. When compared with standard values for sea turtles, the general morphological features assigned the specimen to Caretta caretta, while the shape and coloration of the head and the beak profile fell within the Eretmochelys imbricata range; the front flippers were instead like those of a Chelonia mydas. Moreover, prefrontal scale number was outside the putative parental species’ ranges. The mitochondrial D-loop sequence was from C. caretta, and matched haplotype CC-A2.1, the most common in the Mediterranean. Sequence profiles at three nuclear loci with species-specific substitutions (Cmos, BDNF and R35) revealed only C. caretta variants, thus excluding that the individual was an F1 hybrid. This study highlights the importance of integrating different methodological approaches to understand reproductive animal biology and to set the boundaries for specific morphological traits. In particular, we propose the genetic analysis of a new combination of mitochondrial and nuclear markers as a standard procedure which can be adopted in the identification of sea turtle hybrids.